Effects of Resistance Training and Bowdichia virgilioides Hydroethanolic Extract on Oxidative Stress Markers in Rats Submitted to Peripheral Nerve Injury - Luana Santos Costa; Felipe J. Aidar; Dihogo Gama de Matos; José Uilien de Oliveira; Jymmys Lopes dos Santos; Paulo Francisco de Almeida-Neto; Raphael Fabrício de Souza; Danielle Dutra Pereira; Nuno Domingos Garrido; Albená Nunes-Silva; Anderson Carlos Marçal; Charles dos Santos Estevam; et al. (MDPI AG, 2020)
The objective of this study was to analyze the effects of the combination of resistance training (RT) and the hydroethanolic extract (EHE) of Bowdichia virgilioides as markers of oxidative stress (OS) in rats with peripheral nerve injury (PNI). Rats were allocated into six groups (n = 10): animals without interventions (C), animals with an exposed nerve but without injury, injured animals, trained and injured animals, injured animals that received EHE, and animals that received a combination of RT and EHE. RT comprised the climbing of stairs. EHE was orally administered (200 mg/kg) for 21 days after PNI induction. RT reduced the amount of lipoperoxidation in plasma (14.11%). EHE reduced lipoperoxidation in the plasma (20.72%) and the brain (41.36). RT associated with the extract simultaneously reduced lipoperoxidation in the plasma (34.23%), muscle (25.13%), and brain (43.98%). There was an increase in total sulhydrilyl levels (a) in the brain (33.33%) via RT; (b) in the brain (44.44%) and muscle (44.51%) using EHE; and (c) in the plasma (54.02%), brain (54.25%), and muscle using the combination of RT + EHE. These results suggest that RT associated with oral EHE results in a decrease in OS.